2019
DOI: 10.1111/apt.15533
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis stage is an independent predictor of outcome in primary biliary cholangitis despite biochemical treatment response

Abstract: Summary Background Fibrosis stage predicts prognosis in patients with chronic liver disease independent of aetiology, although its precise role in risk stratification in patients with primary biliary cholangitis (PBC) remains undefined. Aim To assess the utility of baseline fibrosis stage in predicting long‐term outcomes in the context of biochemical risk stratification Methods In a large and globally representative cohort of patients with PBC, liver biopsies performed from 1980 to 2014 were evaluated. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 36 publications
3
48
0
1
Order By: Relevance
“…This highlights that risk in PBC is multifactorial and relates to biochemical response to UDCA in part but also to age and fibrosis stage. ( 14 ) Additionally, further improvement in outcomes with subnormal bilirubin levels and ALP reductions below traditional thresholds has been suggested, emphasizing that improvement in biochemical parameters in this subset of patients is also clinically relevant. Inclusion of such patients in our analysis is a strength as it reflects a cohort of patients at risk who may be ineligible for clinical trials but may respond to and benefit from adjunctive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights that risk in PBC is multifactorial and relates to biochemical response to UDCA in part but also to age and fibrosis stage. ( 14 ) Additionally, further improvement in outcomes with subnormal bilirubin levels and ALP reductions below traditional thresholds has been suggested, emphasizing that improvement in biochemical parameters in this subset of patients is also clinically relevant. Inclusion of such patients in our analysis is a strength as it reflects a cohort of patients at risk who may be ineligible for clinical trials but may respond to and benefit from adjunctive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ALBI score that calculated by bilirubin and albumin showed higher AUROCs than bilirubin alone, suggesting that it could be used as a better prognostic marker by combining them. Previous reports showed that non-invasive fibrosis markers are essential for estimating outcomes in PBC 23,24 . The ALBI and Mayo scores, which include bilirubin, are superior to the FIB-4 index for predicting outcomes, including mortality and liver transplant-free survival, throughout the clinical course of patients with PBC.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐invasive clinical tools such as the AST to platelet ratio index (APRI) and fibrosis‐4 (FIB‐4) score may be helpful in predicting the level of fibrosis, with AUROC of 0.758 and 0.693 for cut‐off values of 0.60 and 1.18, respectively, for distinguishing early vs advanced fibrosis 124 . Patients with evidence of fibrosis or cirrhosis at initial assessment are clearly in the advanced stages of disease and require close specialist monitoring/care, as fibrosis is an independent predictor of survival, even with good biochemical response 125 . Disease severity is also reflected by elevated bilirubin values, decreased platelet count or evidence of end‐stage liver disease such as ascites, variceal bleeding and encephalopathy.…”
Section: How Should I Manage Chronic Liver Disease and Its Associatedmentioning
confidence: 99%
“…Liver biopsy evaluation can equally stage disease but is less frequently used in clinical practice, with late stage disease demonstrating advanced fibrosis alongside ductopenia and/or ductular proliferation on a background of chronic, nonsuppurative destructive cholangitis 126 . PBC patients with stage III/IV advanced histological fibrosis on baseline biopsy (ie with fibrous septa extending beyond triads with portal‐portal bridging or cirrhosis) have an independent predictor of worse outcome, with 10 year survival of 76.0%‐86.6% 125 …”
Section: How Should I Manage Chronic Liver Disease and Its Associatedmentioning
confidence: 99%